Pengaruh Ekspor, Penanaman Modal Asing, Dan Utang Luar Negeri Terhadap PDB Indonesia - Ririn Wigiutami; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2022)
This research was contucted with the aim of analyzing the effect of export, foreign investment, dan foreign debt on Indonesia’s GDP simultaneously or partially. This Study uses a quantitative approach with secondary time series from 2006-2021 obtained from the websites of the World Bank, Bank Indonesia, and the Central Statistics Agency. The analysis technique used is multiple linear regression with the EViews 10 analysis tool. This result of this study indicate that export and foreign Investment (FDI) have no effect on Indonesia’s gross domestic product (GDP) partially. However, foreign debt has a positive and significant effect on GDP. Meanwhile, simultaneously there is a significant influence between the three independent variabel and Indonesia’s GDP.